Mer de Barents, U.R.S.S., baies et mouillages dans le Golfe Motovski / Service hydrographique de la marine . 1940 - France. Service hydrographique de la marine (1946)
Publication provisoire. Corr. . 1946 Relief shown by spot heights. Depths shown by bathymetric isolines and soundings.; Selected lights shown in orange.; Baies Ara et Ura -- Entrée de la baie Ara -- Baie Eina.; Includes blank space (17 x 20 cm) Color;